2018
DOI: 10.5380/rsa.v19i1.51509
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Potassium Fertilization in Creeping Peanut

Abstract: Phosphorus (P) and potassium (K) fertilization can maximize the profitability of peanut cultivation. Therefore, the aim of this study was to evaluate the basic fertilization with P and K on the grain yield and production components of creeping peanut. The experiment was performed in a randomized block design, in a 2 x 3 + 1 factorial scheme. Two doses of K (30 and 60 kg ha-1 of K2O) and three levels of P (60, 90 and 120 kg ha-1 of P2O5) at sowing and an additional treatment without the basic fertilization were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This leads to a negative K balance in the cropping system, which can deplete K in the soil for the peanut crop, as reported by Hoang et al (2019). Zoz et al (2018) reported greater peanut yield with an application of 30 kg ha -1 of K in a clayey soil with K content of 11 mmol c dm −3 (860 kg K ha −1 ). In irrigated areas with sandy soils, maximum peanut yield was observed with application between 50 and 75 kg ha -1 (Hoang et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This leads to a negative K balance in the cropping system, which can deplete K in the soil for the peanut crop, as reported by Hoang et al (2019). Zoz et al (2018) reported greater peanut yield with an application of 30 kg ha -1 of K in a clayey soil with K content of 11 mmol c dm −3 (860 kg K ha −1 ). In irrigated areas with sandy soils, maximum peanut yield was observed with application between 50 and 75 kg ha -1 (Hoang et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Zoz et al. (2018) reported greater peanut yield with an application of 30 kg ha ‐1 of K in a clayey soil with K content of 11 mmol c dm −3 (860 kg K ha −1 ). In irrigated areas with sandy soils, maximum peanut yield was observed with application between 50 and 75 kg ha ‐1 (Hoang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators confirmed such respond to phosphorus. Kabir et al (2013) and recently, Kumar (2017) and Zoz et al (2018) indicated that, increasing the level of phosphoric fertilization leads to an increased number of pods and seeds, weight of pods and seeds and yield in terms of pod, seed and oil of peanut.…”
Section: Effect Of Phosphorus Soil Fertilization Levels Applicationmentioning
confidence: 99%
“…Phosphorus deficiency is known to reduce flower production, size of pods and adversely affect the formation of root nodules (Panwar et al, 2006). In this respect, Kabir et al (2013), Kumar (2017) and Zoz et al (2018) indicated that, increasing the level of phosphorus application increased pod and seed yield and all their attributes of peanut.…”
mentioning
confidence: 99%
“…Phosphorus application in foliar spraying method increase P use efficiency and its uptake by plants, which enhance using of nutrients and assimilates and increase number of filled pods and seed yield (Karma, 2010). Zoz et al (2018) and Mekdad (2019) reported that P played an important role in increasing pod and seed yield of peanut.…”
Section: Peanut Yieldmentioning
confidence: 99%